Urbanization and brood parasitism affect growth, but not free amino acid concentrations in nestling song sparrows (Melospiza melodia) - VanDiest, Isaac J.; Lane, Samuel J.; Fossett, Taylor E.; Sewall, Kendra B. (Frontiers in Bird Science, 2025)
Urbanization is projected to grow rapidly in the coming decades. Several consequences of this form of anthropogenic change for ecosystems and individuals are described by the fields of urban ecology and urban ecophysiology, respectively. Of the environmental variables that could pose challenges for urban-living animals, energy limitations may be especially important, particularly for animals with critical periods of growth, such as nestling songbirds. Many studies document reduced arthropod prey availability for songbirds living in urban habitats, which can compromise the growth and condition of nestlings, possibly because of protein limitation. In our study system of replicate urban and rural song sparrow (Melospiza melodia) populations, there is lower arthropod biomass in urban habitats, as well as higher rates of brood parasitism by brown-headed cowbirds (Molothrus ater), which can cause additional nutritional limitation. Therefore, we hypothesized that urban nestling song sparrows may be protein-limited and experience compromised growth and body condition relative to rural nestlings. We tested this hypothesis with two studies. First, we took body measurements during the first 10 days of development from rural nestlings, urban nestlings without brood parasites, and urban nestlings with brood parasites to see if groups differed in growth (n = 348 nestlings over 6 years). Second, we collected nestling plasma samples (n = 43) from a subset of the birds measured in the first study and then used liquid chromatography-mass spectrometry (LC-MS) to determine concentrations of free amino acids. We found rural nestlings had greater change over time in body mass and tarsus length compared to both urban groups. However, we found no differences in amino acid concentrations across these nestling groups. Thus, urbanization appears to affect growth rates in song sparrows, especially when brood parasites are present in a nest, but we found no evidence supporting amino acids as the mechanistic link for these differences in our system.